Pre-Dominance Herbs Medicine against Alzheimer’s Disease, In Vivo Studies: A Literature Review - Vicko Suswidiantoro; Fikriya Ridlawati; Dewi Damayanti Abdul Karim; Mida Pratiwi; Riza Dwiningrum; Wina Safutri; Diah Kartika Putri; Iga Mayola Pisacha; Kaka Widi Rahayu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Objective: Alzheimer's disease is a progressive, unremitting, neurodegenerative disorder that affects wide areas of the cerebral cortex and hippocampus. Abnormalities are usually first detected in the brain tissue involving the frontal and temporal lobes, then slowly progressing to other areas of the neocortex. The study aimed: to summarise pre-dominance herbs medicine with neuroprotective effects for Alzheimer’s disease. Method: Searching at PubMed (during 2001-2021), the last research was performed in December 2001; relevant websites; and scanning of reference list of relevant articles. There were no language or publication restrictions. Search for keywords in MeSH (medical subject heading) with the words ‘Alzheimer’s disease, dementia, cognitive impairment, in vivo. Results: six plants medicine In vivo preclinical studies founds the medicinal plants have promising potential to prevent Alzheimer's disease. Abstrak: Objektif: Alzheimer yaitu penyakit degeneratif yang berhubungan dengan kerusakan saraf pada area cerebral cortex dan hippocampus. Gangguan ini dapat diketahui atau terdeteksi dari adanya perubahan pada lobus frontal dan temporal serta berkembang menuju neocortex. Tujuan: merangkum keunggulan tanaman obat herbal yang memiliki aktivitas neuroprotektif pada Alzheimer. Metode: pencarian data melalui PubMed (pada rentang tahun 2001-2021), pencarian dilakukan juga terkait penelitian yang relevan. Tidak ada batasan dalam pemilihan Bahasa. Pencarian dilakukan dengan memasukkan kata kunci pada MeSH (medical subject heading) berupa Alzheimer, dementia, gangguan kognitif, in vivo. Hasil: terdapat 6 tanaman herbal yang sudah dilakukan uji prekilins in vivo yang memiliki potensi menjanjika dalam pencegahan terjadinya Alzheimer